Has Regional Hospital Autonomy Achieved Its Goals? Lessons Learned from Indonesia: A Systematic Review - Basabih, Masyitoh; Widhakuswara, Indriaswari (Kesmas, 2025)
This study examined the impact of hospital autonomy implementation on the performance of regional public hospitals in Indonesia, particularly in terms of efficiency, effectiveness, and governance. A systematic review of 32 peer-reviewed studies published between June 12 and September 6, 2023, was conducted using Garba Rujukan Digital and Google Scholar, following PRISMA guidelines. Studies addressing financial performance, service outcomes, and challenges related to implementing autonomy were included. The findings indicated that while autonomy led to improvements in infrastructure, service types, visit volumes, and hospital revenues, it had only a marginal impact on improving key health performance outcomes, such as service efficiency, effectiveness, and overall quality, suggesting the core goals of autonomy had not yet been fully achieved. Key barriers included weak policy capacity, inadequate governance structures, and limited human resources. Unlike centrally managed hospitals, the success of regional hospital autonomy is significantly shaped by local institutional arrangements and the broader decentralization framework, which together influence hospitals’ capacity to manage their operations effectively.